Societal Influence, Leadership and Impact: Deﬁning Traits of Twenty Pioneer Southeast Asian Leaders - Institute for Societal Leadership (Institutional Knowledge at Singapore Management University, 2015)
This study focuses on twenty Southeast Asian leaders who have been key players during critical transitions in the social, economic and political development of their country. In asking each of the societal leaders questions concerning their motivation, the cause they were championing and the factors that have led to their success as leaders, the study attempts to draw out common traits they possess and investigates whether the traits that make people effective societal leaders differ across socio-cultural and historical contexts. A grounded theory approach is used in the analysis of the attributes and traits that emerge from the transcripts of the videotaped interviews. A holistic model is used to capture the causal conditions, varying inﬂuences, strategies, consequences as well as the contexts that led to strong societal leadership.